Digitization, Copyright, and the Welfare Effects of Music Trade - Luis Aguiar; Joel Waldfogel (European Commission, Joint Research Centre (JRC), 2014)
Since the launch of the iTunes Music Store in the US in 2003 and in much of Europe in the following years, music trade has shifted rapidly from physical to digital products, raising the availability of products in di erent countries. Despite substantial growth in availability, the available choice sets of digital music have not fully converged across countries. The territorial fragmentation of the EU copyright management regime and related cross-border transaction costs are often perceived as an obstacle to greater availability. However, other factors such as commercial strategies by music producers may also a ect availability. EU policy makers are now contemplating various possibilities to reduce these cross-border trade costs and improve convergence in music availability across countries. This raises the question of how much bene t these policy measures would create for consumers and producers in Europe and around the world. This study calculates the economic bene ts for consumers and producers from further trade opening or trade cost reductions in digital music. We address this question using comprehensive Nielsen data on digital track sales in the US, Canada, 13 EU Member States, and 2 other European countries (Norway and Switzerland) from 2006 to 2011. We estimate a structural model of music demand which allows us to obtain the consumer surplus for consumers in each destination country as well as the revenue for producers in each origin country. Our model allows us to simulate several scenarios. We rst compare the baseline current situation (the quo") with full autarky whereby only local music is available in each country - a big step backwards compared to the status quo. We then compare the status quo with a fully open EU Digital Single Market whereby all European music is available in all EU countries. Finally, we simulate worldwide openness in which all music is available in all countries. We estimate both consumer surplus bene ts and producer revenue e ects for these scenarios. Not surprisingly, the current status quo music trade bene ts consumers everywhere compared to the autarky scenario. Relative to autarky, status quo trade raises aggregate consumer surplus in the 17 countries by about e300 million (a 11.3% increase). Trade also raises producer revenue by e85 million (a 2.8% increase). European consumers bene t more from music trade than North Americans. However, it has large bene ts for American producers but on balance small bene ts to European producers. American producers have a larger market share in Europe that European producers have in the US. Moving from the current status quo to an EU Digital Single Market for music would increase consumer surplus from digital music consumption by 1.8 per cent (e19 million) and music producers'revenue by 1.1 per cent (e10 million). Bene ts vary considerably across Member States. Under worldwide frictionless trade consumers in 15 European countries gain e31 million (a 3% increase) while North American consumers gain e6.5 million (a 0.35% increase). Most of the gains from fully frictionless trade - about two thirds - are accomplished by a European single market. Annual gains from worldwide frictionless trade for producers, compared to autarky, reach 1.9% in Europe and 0.38% in the US. Clearly, the additional gains from moving beyond a European Digital Single Market to a worldwide open market would be small for European producers and consumers. Digital music production and consumption is only a small part of all media markets covered by copyright. We note that the gures presented here represent only a fraction of the potential bene ts from further trade opening in other digital media.
Keywords: 330; music; digitization; digital media; online markets; downloading; international trade